Impact of ATM Service on Customer Perception and Satisfaction of Indian Banks - Malik, Garima; Bansal, Sanjeev (School of Business and Management Institut Teknologi Bandung, 2015)
Abstract. Indian banking sector has completely changed. It has undergone much technological advancement that makes banking easy. Technological advancements are important but at the end what build customer satisfaction is proper management, employee behavior and customer relationship handling. Customer satisfaction is a sum of many variables that is many factors together leads to customer satisfaction. This modern electronic banking has completely changed the concept and functioning of banking system in India. Indian banking has moved from cash economy to cheque to and finally to the use of plastic cards. The customer satisfaction is dependent on customer awareness to a lot of extent. An unaware customer has less knowledge and therefore they cannot use the facilities completely even if they have it at their disposal. Customers prefer public sector banks when they are looking for trust and security and reliability. When it comes to speed, advancements and up gradation people shits from public sector banks to private sector banks. Customer gets satisfied only when they get quality service from the brand they are dealing with. This is very important for the marketers or the service providers as this leads to consumer satisfaction which benefits them and this brings loyalty to the brand enhancing the brand positioning. This research is important because new modern era has made people technology savvy they start their day with technology and end with technology therefore it is important to see the perception of users towards various factors of ATM. This research is conducted to see the highlighting factors that have direct impact on ATM services. Keywords: ATM, Customer satisfaction, Service quality, Private Banks, Public banks